Comportamiento agronómico y valor nutricional del pasto Brachiaria brizantha con abonos orgánicos en diferentes estados de madurez en el Campo Experimental La Playita UTC- La Maná - Cañizares Cepeda, Carlos Hernán (2014)
This research pretends to know the development of the Brachiaria brizantha using two different organic fertilizers in the Experimental Field La Playita of the Cotopaxi Technical University La Maná, for this purpose it was established planting of B. brizantha in plots of three meters long by one meter wide, a block design completely at random was used (DBCA) with factorial two by four where the factor A (fertilisers: vermicompost and residue from slaughterhouses) and factor B (States of maturity: 30, 45, 60 and 75 days), three replicates were used. The information was collected according to the stages of maturity and sent to the laboratory for their respective analysis of chemical composition....